Pendidikan Karakter Siswa SDN 2 Sukamanah dalam Perspektif Islam - Inayah Ummu Abdullah, Azqya; Sadiah, Siti (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Character education is an effort to shape personality and noble morals in individuals. This is becoming increasingly important in today's modern era, where moral and ethical values ​​are increasingly being eroded. As a result, character education in elementary schools is very important to shape students' morals and morals. The Qur'an as the main source in Islam contains many verses that discuss character education. These verses can be used as guidelines for building a young generation with noble character. This article reviews the development strategy for character education from an Islamic perspective at SDN 2 Sukamanah. This character education program is designed and implemented carefully and carefully to teach students the values ​​of human behavior related to God, fellow humans, the environment and nationality. Through contextual and textual understanding studies, this paper aims to gain an understanding of the character education approach formulated from an Islamic perspective at SDN 2 Sukamanah. In-depth analysis also involves the role of teachers, students and the school environment in encouraging Islamic-based characters. Keyword: Pendidikan Karakter,Akhlak,Islam